Team building in sport: A narrative review of the program effectiveness, current methods, and theoretical underpinnings - Rovio, E.; Arvinen-Barrow, M. M.; Weigand, D. A.; Eskola, J.; Lintunen, T. (The Sport Psychologist, 2011)
Despite team building (TB) methods having their roots in organizational development (OD), this theoretical background has been seldom applied in sport. The purpose of this study was to provide chronological narrative review of the recent (1997-2008) sport-related research on team building. A total of 28 articles were reviewed. The findings suggest that team building has a positive effect on group functioning, especially increasing group cohesion. It was also apparent that thus far, the team building research in sport is mostly focused on cohesion. In conclusion, it would be advantageous for researchers to familiarize themselves with the existing organizational development research tradition. This could assist in establishing a clear definition and a solid theoretical framework for team building in sport, as well as preventing sport researchers making the same mistakes made in work organizations. By doing so, team building, and the development of group functioning and performance, could become an even more promising area for sport science research.